2001
DOI: 10.1046/j.1365-2869.2001.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of penile erections during paradoxical sleep. Peculiar penile events during wakefulness and slow wave sleep in the armadillo

Abstract: The electroencephalogram (EEG) together with electromyogram (EMG) of the ischiocavernosus, bulbocavernosus and levator penis muscles were chronically monitored across behavioral states of the armadillo Chaetophractus villosus. This animal has a very long penis, which exhibits remarkable phenomena during wakefulness (W), slow wave sleep (SWS) and paradoxical sleep (PS). During W it remains retracted within a skin receptacle. During SWS penile protrusion can be observed together with very complex movements. Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 10 publications
(8 reference statements)
0
26
0
Order By: Relevance
“…In phylogeny, this function of REM sleep is advantageous to explain the various exceptions of REM sleep, especially the absence of REM sleep in dolphins (Cai, 2015b;Lyamin et al, 2007;Madan & Jha, 2012;Sekiguchi et al, 2006;Siegel, 2008) and short duration of REM sleep in birds (Ayala-Guerrero et al, 1988Cai, 2015b) in contrary to that in humans (Cai, 2015b;Floyd et al, 2007) and rodents (Cai, 2015b;Rechtschaffen et al, 1989), the absence of penile erections in REM sleep in armadillo (Affanni et al, 2001;Cai, 2015b), as well as the higher voltage in EEG during REM sleep in platypus (Cai, 2015b;Siegel et al, 1998;1999) and ostrich (Cai, 2015b;Lesku et al, 2011). In physiology, this function of REM sleep is advantageous to explain the association of REM sleep with the atonic episodes in SWS (Cai, 2015b;Tinguely et al, 2006;Werth et al, 2002), the absence of drastic menopausal change in duration of REM sleep (Cai, 2015b;Kalleinen et al, 2008;Orff et al, 2012;Shaver et al, 1988), and the different effects of ambient temperature on duration of REM sleep in rodents (Amici et al, 1998;Cai, 2015b;Rosenthal & Vogel, 1993;1994;Roussel et al, 1984) and humans (Cai, 2015b;Haskell et al, 1981;Karacan et al, 1978).…”
Section: The Peripheral Functions Of Rem Sleepmentioning
confidence: 99%
See 2 more Smart Citations
“…In phylogeny, this function of REM sleep is advantageous to explain the various exceptions of REM sleep, especially the absence of REM sleep in dolphins (Cai, 2015b;Lyamin et al, 2007;Madan & Jha, 2012;Sekiguchi et al, 2006;Siegel, 2008) and short duration of REM sleep in birds (Ayala-Guerrero et al, 1988Cai, 2015b) in contrary to that in humans (Cai, 2015b;Floyd et al, 2007) and rodents (Cai, 2015b;Rechtschaffen et al, 1989), the absence of penile erections in REM sleep in armadillo (Affanni et al, 2001;Cai, 2015b), as well as the higher voltage in EEG during REM sleep in platypus (Cai, 2015b;Siegel et al, 1998;1999) and ostrich (Cai, 2015b;Lesku et al, 2011). In physiology, this function of REM sleep is advantageous to explain the association of REM sleep with the atonic episodes in SWS (Cai, 2015b;Tinguely et al, 2006;Werth et al, 2002), the absence of drastic menopausal change in duration of REM sleep (Cai, 2015b;Kalleinen et al, 2008;Orff et al, 2012;Shaver et al, 1988), and the different effects of ambient temperature on duration of REM sleep in rodents (Amici et al, 1998;Cai, 2015b;Rosenthal & Vogel, 1993;1994;Roussel et al, 1984) and humans (Cai, 2015b;Haskell et al, 1981;Karacan et al, 1978).…”
Section: The Peripheral Functions Of Rem Sleepmentioning
confidence: 99%
“…In a few species, sleep is very long in duration, such as the armadillo (Affanni et al, 2001), bat (Zhao et al, 2010), owl monkey (Sri Kantha et al, 2009;Suzuki & Sri Kantha, 2006), and so on, so that immobility is obviously their natural adaption. Nonetheless, Lesku et al recently proposed that the REM sleep manifested inverse correlation with predation risk in most species (Lesku et al, 2006;.…”
Section: The Peripheral Functions Of Rem Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains ambiguous whether the echidna has combined aspects of REM and NREM sleep or no REM sleep because only one study has reported some of the typical characteristics of REM sleep [38] . [39,40] , while the large hairy armadillo usually sleeps 20 h/day [41] . It can also be argued that animals that sleep less would exhibit less REM sleep.…”
Section: Continuedmentioning
confidence: 99%
“…Several species of this family, such as the giant armadillo (Priodontes maximus), are in danger of extinction (IUCN 2006). They are a model of interest in many fields because of exclusive aspects of their anatomy (Wetzel 1985b;Galliari et al 2009), physiology (Roig 1969(Roig , 1970Galbreath 1985;Storrs & Burchfield 1985;Cetica et al 1993Cetica et al , 1997Cetica et al , 2005Casanave & Affanni 1994;Affanni et al 2001), biology (Vizcaino & Loughry 2008) and their relatively antique biogeographic position in South America (Wetzel 1985a).…”
Section: Introductionmentioning
confidence: 99%